Evaluación de una membrana bioabsorbible y verificación de la neoformación ósea en procedimientos de exodoncia atraumática - Caparroso-P., Carlos; Ramírez-S., Julián; Becerra-S., Fabio; Henao-C., Cecilia (Revista Facultad de Odontología Universidad de Antioquia, 2017)
This stud • presents the results of the eiraluation of a bioabsorbible membrane and the confirmation of the bone rid,:rje regeneration in atraumatic extraction procedures. _'Vine patients who required one or more ek tractions from premolar to preim•Vaz- were utilized in this study . Ten ex-traction sites were asi:_qiied to the Contro17roup,lnd a !ter atra Ulna tic' extraction, the bucal Hap was corona positioned to cor-or completely the alveolus_ In the ten e.xpernrental sites the same procedure was performed, but the bioabsorbible membrane was placed to a?i rer the alveolus, before the flap was positioned. .411 the sites were clinically and radiograficallv evaluated in thickne5s and lie! ht during to"entv four weeks.. In the evperimental sites soft tissues incisional biopsies wore taken On 3, 5, 7, 9 11, 13, 15, 17, 19 and 21 weeks from the edentulus ridere, to study histalo,:.-ricallv the bioabsoiption of the membrane and to see the tissue reaction to it. There WaS a small difference between eyerimental and control groups in thickness and height values, .f:71rorable to the experimental group but it [las not statistically signiticati All sites presented a reduction in the two studied dimensions. The bioabsorbible membrane did not induce a strong inflaniniatoziv tissue reaction and it li'as not possible to identity it in the histological samples, even in the third week cif hict(lIL1gic X31 examination.